MACROSTRUCTURE OF CLASSROOM SPOKEN DISCOURSES PRODUCED BY ENGLISH TEACHERS - Meta Keumala; Iskandar Abdul Samad; Dohra Fitrisia (English Education Journal, 2020)
For English teaching practice, it is important to deliberate productive talks that spur students’ comprehension, creativity, and problem solving ability. This research aimed at finding out the spoken discourse based on six phases of macrostructure in English classrooms. In this study, the writers employed observation guide sheets to collect the data and it was employed to 2 English teachers in Aceh Besar. The guide was developed based on Van Dijk (1980) on macrostructure in discourse society. The theory was adopted and adjusted based on the classroom spoken discourse. The data were analyzed using the interactive model analysis by Miles, Huberman, and Saldana (2014). The steps were data condensation, data display, and data verification by using a percentage formula. The findings indicate that two teachers conducted the process of teaching and learning activities according to the lesson plans that they had previously designed. Even though both of them had different teaching strategies, but the lesson plans had a complete structure with 6 steps in macro-phases.